OPTIMALISASI PENCEGAHAN ANEMIA PADA REMAJA PUTRI MELALUI KOMBINASI SUPLEMENTASI ZAT BESI DAN JUS LEMON - Beny Arnita; Ristika Ristika (Jurnal LENTERA, 2026)
Anemia among adolescent girls remains a common health problem caused by menstruation, inadequate iron intake, and low adherence to iron supplementation consumption. One effort to improve iron absorption is by combining iron supplementation with lemon juice containing vitamin C. This community service activity aimed to help improve hemoglobin levels among adolescent girls through the combination of iron supplementation and lemon juice administration. The methods included health education, hemoglobin level examination, administration of iron tablets combined with lemon juice, and consumption assistance involving 15 adolescent girls in Bandar Surabaya Village, Bandarjaya District, Central Lampung in 2025. Evaluation was carried out by measuring hemoglobin levels before and after the intervention during the activity. The results showed that the average hemoglobin level increased from 10.8 g/dL before the intervention to 12.4 g/dL after the administration of iron tablets combined with lemon juice. A total of 80.0% of participants experienced increased hemoglobin levels after the intervention. This activity demonstrates that the combination of iron supplementation and lemon juice can help improve hemoglobin levels and support anemia prevention efforts among adolescent girls